Congenital cystic adenomatoid malformation type I - Alice Rebelo de Matos Borges dos Reis; Frederico Becker Ribeiro; Regina Schultz (University of São Paulo, 2015)
Congenital cystic adenomatoid malformation (CCAM) is an hamartomatous congenital pulmonary airway malformation with incidence ranging between 1:10,000 and 1:35,000 newborns. Currently CCAM is classified into five groups according to clinical and pathological features. The clinical outcome varies depending on the subtype and the extent of involvement. The authors report the case of a premature male newborn with the prenatal diagnosis of CCAM Type 1 associated with cardiac right axis deviation, who died 67 hours after birth due to respiratory failure. In addition to the autopsy report of this rare entity, the authors present its classification and prognosis.